Fishermen’s Perspective on Herpetofauna: A Case Study from Kuala Tungkal, Tanjung Jabung Barat, Jambi - Kurniawan, Nia; Firdaus, Anggun Sausan; Nugraha, Fitra Arya Dwi; Maulidi, Andri; Kurnianto, Aguung Sih (Journal of Tropical Life Science, 2018)
The population of herpetofauna (Class: Reptilia, Amphibia) is continuously declining throughout the world. Moreover, habitat changes such deforestation drive rapidly to declining process. Human communities play an important role in conserving the herpetofauna by maintaining and improving the harmonious relationship between human and environment. Therefore, these association will strongly support the conservation of herpetofauna and their habitats. This study is aimed to survey the herpetofauna communities, explore the local people perspective on herpetofauna, and the relationship between human and herpetofauna. We found 12 species observed in this survey that included to 3 order of herpetofauna: anura, squamata and testudines. Local people recognized herpetofauna species around them well and do not harm them because of their roles, such as part of nature (39%), bioindicator (33%), myth (17%), and economic value (11%). We also revealed the local knowledge on herpetofauna, as 14 local names and their roles. Despite Kuala Tungkal is a strategic area for the national port development that probably impacts herpetofauna microhabitat, it needs serious attention on herpetofaunal issues.